Sustainability reporting, gender diversity, firm value and corporate performance in ASEAN region - Rojana Khunkaew; Jittima Wichianrak; Muttanachai Suttipun (Cogent Business & Management, 2023)
This paper aimed to examine the influences of sustainability reporting and gender diversity on corporate outcomes of listed companies in ASEAN region. The listed companies in ASEAN region consisting of Thailand, Malaysia, Indonesia, and the Philippines during 2010 to 2019 were used as population and sample of this study. Seven key performance indexes of the Global Reporting Initiative (GRI) Standards, Carbon Disclosure Project (CDP), Carbon Knights, and Refinitiv were used to measure the extent and level of sustainability reporting, while the proportion of female board committee was used to measure gender diversity, and firm value measured by Tobin's Q and firm performance measured by return on asset (ROA) were used as the proxies of corporate outcomes. The sequential logit regression models were developed to test the hypotheses used in this study. This study found positive impact of energy used, water management, work safety, and gender diversity on corporate performance, while corporate performance was influenced by carbon emission and waste management negatively. Moreover, gender diversity moderated the negative relationship between energy used, water management, work safety, and corporate performance. On the other hand, there was water management, and work safety influencing firm value positively, while waste management had negative impact on firm value. However, gender diversity did not moderate any relationship between sustainability reporting and firm value. The study findings benefit to top management who may encourage in sustainability reporting especially water management and work safety to enhance the corporate performance and value.
Keywords: M40; M41; M48; 650; ASEAN region; corporate performance; firm value; gender diversity; sustainability reporting